A sustentabilidade na formação atual do arquiteto e urbanista - Dianna Santiago Villela (2007)
The objective of this work is to analyze if sustainability has been sufficiently discussed through the architect and urban designers formation. Although largely used, the vast concept of sustainability lacks precision and content. The effort to explain it is based ondefinitions, as well as on the previous trends to the concept. The architecture undergraduate program of some Brazilian universities is searched in order to investigate the current influence ofsustainability in the architect's education. Also, environmental education is discussed to emphasize the importance of learning sustainability for the architect's and city planner's intellectual growth. Lastly, the results of an interview with architecture students, architects, and Opera Prima awarded students (between 2001 and 2006) are presented showing through the young architects opinions how the discussion about sustainability has been perceived in architecture and urban design programs. The results show that sustainability has not been enoughdiscussed in the undergraduate courses. It can and probably is affecting the architect and urban designers formation since they graduate without a global vision about the subject. The ones especially interested in this topic look for graduate courses in this area. Architects and studentsinterviewed have the common belief that the architects formation should include issues about sustainability since these are important issues for improvement of human life quality and its full integration with nature. This topic should be a priority in the basic professional education andnot restricted to elective classes and graduate programs.